A prospective comparison of MRI‐US fused targeted biopsy versus systematic ultrasound‐guided biopsy for detecting clinically significant prostate cancer in patients on active surveillance. Issue 1 (21st July 2014) - Da Rosa, Michael R.; Milot, Laurent; Sugar, Linda; Vesprini, Danny; Chung, Hans; Loblaw, Andrew; Pond, Gregory R.; Klotz, Laurence; Haider, Masoom A.
<x xml:space="preserve">Abstract</x> Background In active surveillance (AS) patients: (i) To compare the ability of a multiparametric MRI (mpMRI)‐ultrasound biopsy system to detect clinically significant (CS) prostate cancer with systematic 12‐core biopsy (R‐TRUSBx), and (ii) To assess the predictive value of mpMRI with biopsy as the reference standard. Methods Seventy‐two men on AS prospectively underwent 3T mpMRI . MRI‐ultrasound fusion biopsy (UroNavBx) and R‐TRUSBx was performed. CS cancer was defined using two thresholds: 1) GS ≥ 7 (CS7) and 2) GS = 6 with >50% involvement (GS6). CS cancer detection rates and predictive values were determined. Results CS7 cancers were found in 19/72 (26%), 7 (37%) identified by UroNavBx alone, 2 (11%) by R‐TRUSBx alone (P = 0.182). UroNav targeted biopsy was 6.3× more likely to yield a core positive for CS7 cancer compared with R‐TRUSBx (25% of 141 versus 4% of 874, P < 0.001). Upgrading of GS occurred in 15/72 patients (21%), 13 (87%) detected by UroNavBx and 10 (67%) by R‐TRUSBx. The NPV of mpMRI for CS7 cancer was 100%. MRI suspicion level significantly predicted CS cancer on multivariate analysis (OR 3.6, P < 0.001). Conclusion UroNavBx detected CS cancer with far fewer cores compared with R‐TRUSBx, and mpMRI had a perfect negative predictive value in this population. J. Magn. Reson. Imaging 2015;41:220–225. © 2014 Wiley Periodicals, Inc.